2002
DOI: 10.3136/fstr.8.178
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Molecular-Weight Glutenin Subunits with Different Protein Contents on Bread-Making Quality.

Abstract: The objective of this study was to evaluate the effects of high-molecular-weight glutenin subunits with different protein contents on the quality of flour. The flour properties of near isogenic lines (NILs), which were substituted with HMWG subunits at the Glu-B1 or Glu-D1 allele, were investigated with four levels of protein content. The effect of the addition of subunits 20 at the Glu-B1 to subunits 5+10 at the Glu-D1 allele on bread-making quality was poor. The strength of the dough was only slightly affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
(14 reference statements)
0
3
0
1
Order By: Relevance
“…In the current study, the authenticity of the 1Ay gene from wild emmer was confirmed by heterogeneous expression ( Figure 3 B) and it was stably expressed in common wheat introgression line TaAy7-40. We demonstrated that TaAy7-40 was significantly superior to its female parent CN16 for not only the SDS sedimentation value and wet gluten content in Chongzhou but also for the three PQPs in Wenjiang ( Figure 7 ) even though they had the same positive effect HMW-GS combination 1Dx5 + 1Dy10 [ 56 ]. These differences might to a certain extent have resulted from the various HWW-GSs at the Glu-1A locus besides those at the Glu-1B locus, because TaAy7-40 had the added novel subunit 1Ay besides the newly substituted subunit 1By8.1 compared with CN16.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the authenticity of the 1Ay gene from wild emmer was confirmed by heterogeneous expression ( Figure 3 B) and it was stably expressed in common wheat introgression line TaAy7-40. We demonstrated that TaAy7-40 was significantly superior to its female parent CN16 for not only the SDS sedimentation value and wet gluten content in Chongzhou but also for the three PQPs in Wenjiang ( Figure 7 ) even though they had the same positive effect HMW-GS combination 1Dx5 + 1Dy10 [ 56 ]. These differences might to a certain extent have resulted from the various HWW-GSs at the Glu-1A locus besides those at the Glu-1B locus, because TaAy7-40 had the added novel subunit 1Ay besides the newly substituted subunit 1By8.1 compared with CN16.…”
Section: Discussionmentioning
confidence: 99%
“…Takata et al (2002) reported that the subunits 2.2 + 12, encoded by the Glu-D1f allele, exerted the most negative effect on dough strength, compared with the subunits encoded by other Glu-D1 alleles. Using materials with similar protein content, we found that the SDS-sedimentation volume of the NILs with the Glu-D1d allele was significantly higher than that of the corresponding recurrent parents (Table 2), suggesting that the Glu-D1d allele exerted a positive effect on dough strength.…”
Section: Discussionmentioning
confidence: 99%
“…They share subunits 2 + 12, 2.2 + 12, or 4 + 12 at the Glu-D1 locus (Nakamura et al 1999). Takata et al (2002) reported that these subunits exerted negative effect on dough strength compared with subunits 5 + 10. They also reported that subunits 2.2 + 12, encoded by the Glu-D1f allele, exerted the most negative effect on dough strength.…”
Section: Introductionmentioning
confidence: 99%
“…グリアジンをコードする対立遺伝子のうち Gli-1 は Glu-3 と連鎖しており, Gli-2 は第 6 同祖群の短腕に位置する. HMW-GS と製パン性の関係についてはこれまでに多くの 研究が行われてきたが Glu-D1 座の対立遺伝子のうち, Glu-D1d がコードする 5+10 が生地物性を強くする効果 が高い事が明らかにされている (Payne et al 1981, Moonen et al 1982, Lawrence et al 1987 .一方,Glu-A1 座の欠失 型(null)は製パン性を低下させることが明らかになっ ている (Payne et al 1979, Moonen et al 1982 (Takata et al 2000(Takata et al , 2002 Table 4.…”
unclassified